2004
DOI: 10.1590/s0101-31222004000100012
|View full text |Cite
|
Sign up to set email alerts
|

Padrões eletroforéticos da enzima alfa-amilase em sementes de milho submetidas a alta temperatura de secagem

Abstract: Importantes mudanças fisiológicas e bioquímicas têm sido estudadas em sementes de milho submetidas a alta temperatura de secagem. O objetivo dessa pesquisa foi avaliar o efeito da secagem a alta temperatura nos padrões eletroforéticos da enzima a -amilase em sementes de linhagens, de híbridos simples e respectivos recíprocos. As sementes foram colhidas com teor de água de aproximadamente 35% e secadas a 45º C. A qualidade fisiológica das sementes de cada material foi avaliada pelo teste de germinação e a enzim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
(19 reference statements)
1
6
0
Order By: Relevance
“…These authors claim that during the seed maturation phase, analysis of reserve material accumulation through molecular markers may allow assessment of seed quality, and that α-amylase activity has been used as marker for desiccation tolerance in maize seeds. This result is in agreement with that of José et al (2004b), in which isoenzymatic proiles for α-amylase showed a higher bandwidth for lineage and hybrid seeds that are tolerant to high drying temperature. Further, Andrade et al (2013) also found expression of these enzymes in in relation to heat resistance in maize seeds.…”
Section: A Lopes Et Alsupporting
confidence: 90%
See 2 more Smart Citations
“…These authors claim that during the seed maturation phase, analysis of reserve material accumulation through molecular markers may allow assessment of seed quality, and that α-amylase activity has been used as marker for desiccation tolerance in maize seeds. This result is in agreement with that of José et al (2004b), in which isoenzymatic proiles for α-amylase showed a higher bandwidth for lineage and hybrid seeds that are tolerant to high drying temperature. Further, Andrade et al (2013) also found expression of these enzymes in in relation to heat resistance in maize seeds.…”
Section: A Lopes Et Alsupporting
confidence: 90%
“…Some research has shown that the physiological quality of maize seed (Zea mays) is inluenced not only by environmental factors, but also by the genotype and its interactions with the environment Importance of amylases in seed quality (HOECKER et al, 2006;REIS et al, 2011;OLIVEIRA et al, 2013;. Many authors such as Rood et al (1990), Causse et al (1995), Gomes et al (2000), José et al (2004b), Hoecker et al (2006 and Reis et al (2011) relate quality to the inluence of heterosis or hybrid vigor in seed germination. In several of these studies, hybrid plants were found to have more eficient enzyme systems compared to other lineages.…”
Section: Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Seeds of Pisum sativum were sensitive to temperature higher than 40 ºC (Siddique and Wright, 2003), while the ones of Jatropha curcas had the electrical conductivity increased at 60 ºC, but only at 70 ºC the germination decreased (Ullmann et al, 2010). According to José et al (2004), the tolerants lines of Zea mays seeds to high temperature had no significant differences in enzyme activity for shade-dried seeds or artificially dried seeds.…”
Section: Resultsmentioning
confidence: 99%
“…These markers can be affected by many environmental factors and especially by stress. In contrast, heat resistant proteins are potential markers that do not present any known catalytic activity (Silva-Mann et al, 2002) presenting polymorphism and stability in seeds, such as in maize (Roveri José et al, 2004).…”
Section: Introductionmentioning
confidence: 99%